Kebijakan Hukum dalam Menanggulangi (Over Criminalization) Korupsi Dana Desa Untuk Mewujudkan Keadilan Restoratif - Rodhi Agung Saputra; Rita Susanti; Bonifa Refsi (Wajah Hukum, 2023)
This study examines the existence of the prosecution authority in Indonesia which is closely related to the Legal Policy in Overcoming (Over Criminalization) Corruption in the Village Fund to realize restorative justice. This needs to be done considering the very large amount of Fund Allocation from 2018-2021 which reached IDR 72 trillion which was intended for 83,381 villages and was very vulnerable to corruption. The problem that will be discussed in this research is How is the Legal Policy in Overcoming Corruption (Over Criminalization) of Village Fund Corruption to realize restorative justice. The research method used is a normative research method with a statute approach and analyzed using content analysis.